Comrades and curators. Issue 4 (2nd October 2019) - McDougall, Julian
Abstract: This article shares the findings of a visual literacy project with museum curators and film educators. The research explores the mediation of social history and politics, the interplay of personal and professional curation and the role of reflexive visual literacy in understanding mediated identities. The project connected three museums around Comrades, the Bill Douglas film about the Tolpuddle Martyrs. First, this article explores the relationship between Comrades as a film text, the curation of the director's collection of magic lanterns and other optical artefacts, the situating of a lanternist as pivotal to the representation of social history in the film and the different curations of this social history in the museums in Exeter, Tolpuddle and Dorchester. Second, it shares the findings of a visual literacy fieldwork intervention, where films were used by the three museum curators and a film academics' network to 'map' their mediated identities and curational practices with a particular focus on personal and professional transformations.